Determinan Nilai Ekspor Jasa Transportasi di Negara-Negara ASEAN - Subriandi, Askar; Oktora, Siskarossa Ika (National Research and Innovation Agency, 2024)
Transportation services are the most significant contributor to the deficit in the Association of Southeast Asian Nations (ASEAN) services trade. From 2016 to 2019, eight out of ten countries in the ASEAN still experienced a trade deficit in transportation services. So that this condition does not drag on in a continuous deficit, one of the policies that each country can carry out is to increase the export performance of transportation services. This study aims to determine the factors that affect the export of transportation services in ASEAN. The secondary data used is trade flow data from 2012 to 2019 from the ASEAN Secretariat and World Bank. The method used is panel data regression with the Random Effect Model (REM). The result found that foreign direct investment, exports of goods, and value-added services significantly affect exports of transportation services in ASEAN. Meanwhile, internet users and exchange rates do not substantially affect exports of transportation services in ASEAN. The results of this study recommend continuing to improve the climate for ease of investment. In addition, it is essential to utilize resources that can increase the production of transportation services and maintain the availability of raw materials and capital goods.